The Annotated Ring Cycle: Twilight for the Gods (Götterdämmerung) - Walter, Frederick Paul (Rowman & Littlefield Publishers, 2022)
Richard Wagner’s magnum opus meets the celebrated translator of Jules Verne novels in this colorful and original work. Frederick Paul Walter makes Twilight for the Gods accessible not only to scholars and opera buffs but also to fans of Tolkien, Star Wars, and Hogwarts through a dazzling new translation in lively modern English and annotations that spotlight the libretto, lyrics, and stage directions. The translation conveys Wagner’s humor, rhymes, alliterative effects, subliminal messages, and inventive tale spinning, plus it also gets the most basic ingredient right: the actual story! It highlights the motives, secrets, and plot twists—what’s really going on and what its narrative shows. Accompanying the translation and annotations are dozens of photos of classic artwork by Arthur Rackham, Howard Pyle, Aubrey Beardsley, the 1876 costume and set designs, and much more.